2007
DOI: 10.3171/spi.2007.6.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cross-linked hyaluronic acid hydrogels on neurite outgrowth and recovery from spinal cord injury

Abstract: Object Therapies that use bioactive materials as replacement extracellular matrices may hold the potential to mitigate the inhibition of regeneration observed after central nervous system trauma. Hyaluronic acid (HA), a nonsulfated glycosaminoglycan ubiquitous in all tissues, was investigated as a potential neural tissue engineering matrix. Methods Chick dorsal root ganglia were cultured in 3D hydrogel m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 40 publications
0
81
0
Order By: Relevance
“…[16][17][18][19] As their pores and channels are artificial, it is difficult to completely simulate the conduction channels of normal spinal cords. Moreover, these scaffold materials have their respective disadvantages, such as degradation products that are unfit for neuronal survival and axonal regeneration; low adhesiveness of cells; and much poorer biological and physical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] As their pores and channels are artificial, it is difficult to completely simulate the conduction channels of normal spinal cords. Moreover, these scaffold materials have their respective disadvantages, such as degradation products that are unfit for neuronal survival and axonal regeneration; low adhesiveness of cells; and much poorer biological and physical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major challenges facing researchers in this area is stimulation of guided axonal extension (Norman et al 2009). To this end, Horn et al (2007) encapsulated chick dorsal ganglia in HA and fibrin gels which were evaluated both in vitro. Both gels were shown to support neutrites within the first 60 h, but after 192 h a 50% increase in neutrite length was seen in HA gels when compared with the fibrin gels.…”
Section: Neural Tissuementioning
confidence: 99%
“…instead, it is combined with other supportive materials to enhance growth promotion [35,39,52,53] and cell differentiation [54] . Recently, it was shown that the [86] iHC [31,32,38] Bladder function [31,32] BBB [87] inclined plane [87] Walking movements [40] Reflexive behaviors [40] Climbing ability [40] Electrophysiology [40] BBB [49,88] Combined behavior score [88] iHC [49,88] Robotic recording [88] Von Frey filaments [89] iHC [62,[89][90][91] Horizontal ladder [91] Beamwalk [91] BBB [70,71,92] inclined plane [70] Von Frey [70] iHC [70,92,93] Electrophysiology [70,72] Structural MRi [70] BBB [85,94,95] iHC [85,94,95] Electrophysiology …”
Section: Polymersmentioning
confidence: 99%
“…Modified HA supports cell attachment and migration, and when combined with brain-derived neurotrophic factor, may improve regeneration and motor function as an implanted scaffold after SCi [70,71] . Due to its natural role as a structural component in the CNS, it has been used both alone as well as in functionalized and combination formats to provide structure and guidance for regenerating axons after injury [71,72] . [19] .…”
Section: Polymersmentioning
confidence: 99%
See 1 more Smart Citation